Pharmacotherapeutics of SARS-CoV-2 Infections - Kevadiya, Bhavesh D. (J Neuroimmune Pharmacol, 2021)
The COVID-19 pandemic has affected more than 38 million people world-wide by person to person transmission of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Therapeutic and preventative strategies for SARS-CoV-2 remains a significant challenge. Within the past several months, effective treatment options have emerged and now include repurposed antivirals, corticosteroids and virus-specific antibodies. The latter has included convalescence plasma and monoclonal antibodies. Complete viral eradication will be achieved through an effective, safe and preventative vaccine. To now provide a comprehensive summary for each of the pharmacotherapeutics and preventative strategies being offered or soon to be developed for SARS-CoV-2. GRAPHICAL ABSTRACT: [Image: see text]